GOOD GOVERNANCE OF KOPERASI WANITA SERBA USAHA â€œSETIA BUDI WANITAâ€ JAWA TIMUR - Puspitasari, Devy Sylvia; Ludigdo, Unti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This research was conducted to understand the implementation of good governance on Koperasi Wanita Serba UsahaÂ â€œSetia Budi Wanitaâ€Â Jawa Timur. Cooperative is economic organization that based on sense of family. Womenâ€™s Cooperative in the present society with the purpose to achieve the welfare of members and society with profesionalism, independent woman, qualified and integrity. This type of researchÂ isÂ aÂ qualitative descriptive method. Instruments used in data collection are interviews, observation, and documentation.Â The results of the research represent passage of the good governance principles includes of transparencyÂ in the provisioningÂ informationÂ for administrators, employees, PPL, PJ, members in a transparent and opened, so that everyÂ employeeÂ alreadyÂ knowsÂ how theÂ systemÂ that are withinÂ the cooperative principleÂ accountibility.Â While,Â the principleÂ ofÂ responsibilityÂ shownÂ SBW towards employees by providing a range of benefits, health insurance, safety and social responsibilityÂ to theÂ society. ThenÂ the principle ofÂ independencyÂ showed nothing intervention from the internal, but external side there is a little ideological andÂ philosophicalÂ differencesÂ cooperative.Â Finally, theÂ FairnessÂ principle, shareholders (members) receive equal and fair treatment in the implementation of the RAT and the division SHU, stakeholders of the employees who were recruited based on their expertise, so the company does not discriminate against employees based on racial and establish a system of reward and punishment is fair. Key Word : Cooperative, Good Governance